Effect of Entecavir Combined with Adefovir Dipivoxil on Clinical Efficacy and TNF-α and IL-6 Levels in Patients with Hepatitis B Cirrhosis. (25th August 2021) - Yu, Yonghuan; Cui, Xinfeng; Zhao, Jingjing; Jia, Ting; Ren, Baofeng; Zhang, Xiaoyan
Abstract : Objective . The purpose of the study was to investigate the effect of entecavir combined with adefovir dipivoxil on clinical efficacy and TNF- α and IL-6 levels in patients with hepatitis B cirrhosis. Methods . A total of 100 patients with hepatitis B cirrhosis admitted to our hospital between January 2018 and June 2019 were randomly selected and divided into the control group ( n = 50) and experimental group ( n = 50) according to the order of admission. Among them, the control group patients were treated with entecavir, while the patients in the experimental group received entecavir combined with adefovir dipivoxil. After that, the effective rate of treatment, the incidence of adverse reactions, liver function indexes, liver fibrosis condition, and TNF- α and IL-6 expression levels were all compared between the two groups. Results . The effective rate of treatment in the experimental group was significantly higher than that in the control group, with statistical significance (p < 0.001 ); the incidence of adverse reactions of the patients in the experimental group was significantly lower than that in the control group, with statistical significance (p < 0.001 ); the liver function indexes in the experimental group were significantly better than those in the control group, with statistical significance (p < 0.001 ); the number of patients with liver fibrosis in the experimental group was significantly less than that in the control group, with statistical significance (p < 0.001 ); the TNF- α and IL-6 expression levels in the experimental group were significantly lower than those in the control group, with statistical significance (p < 0.001 ). Conclusion . Entecavir combined with adefovir dipivoxil in the treatment of hepatitis B cirrhosis can effectively improve the therapeutic effect and reduce the serum inflammatory factor levels, with high safety, which is worthy of application and popularization.